Hubungan Motivasi Belajar terhadap Prestasi Belajar IPA Terpadu - Dase Nasrudin Syah; Ahmad Amin; Ovilia Putri Utami Gumay (SPEJ (Science and Physic Education Journal), 2019)
the purpose of this study was to learn that the relationship between learning motivation towards integrated science learning achievement of class VIII students. The research method used is document research. The population is all Class VIII Students Mazro'illahLubuklinggau are 61 students and the only sample of one class to be randomized is Class VIII. Tecnicquecollecution is the questioner. The data collection technique of this study used a questionnaire or questionnaire and documentation method. The correlation between the second variable (rxy) is 01,5203 (valid conversion coefficient). The question posed is motivation with learners is a = 31.65 and b = 0.77, so the regression is Y = 31.65 + 0, 77X. B value is positive, is positive learning motivation because of student results. The resulting linearity is 6.91 and the distribution is α = 0.05. Statistical value = 7.029> t table 2.05. Significance (α = 0.05) and degrees of freedom are (n-2), so that the hypothesis can be used t count> t table (7.029> 2.05). Saint Complienced's results were 53.4% ​​and the residue was 46.6% from the others. Try learning to learn significantly with Saint Complect MTs Mazro'illah Lubuklinggau in 2016/2017. Keyword: Motivation, Lean Result